Evaluation of acid stage and of hydrogen peroxide on alkaline extraction of eucalyptus kraft pulp - Dos Santos, Rafael; Da Silva, Luana Oliveira [UNESP]; Caraschi, José Cláudio [UNESP] (My University, 2017)
The Elemental Chlorine Free (ECF) bleaching technology is very well established for kraft pulp bleaching due to its efficiency in bleaching processes, once it presents high brightness, besides low reversion. In this work several analyses were accomplished from oxygen-delignified kraft pulp which were submitted to four different ECF bleaching sequences: OD0ED1P, ODo(E+P)D1P, OAhtD0ED1P and OAHTD0(E+P)D1P. Bleached pulps were analyzed concerning their properties, and also their bleaching cost. It was verified that pulps submitted to the alkaline extraction stage with hydrogen peroxide (H2O2) presented final brightness slightly higher compared to the pulps which has been treated by an alkaline extraction stage without using hydrogen peroxide. Through kappa number analysis it has been noticed that pulps treated by a high temperature acid stage (AHT) presented lower kappa number, possibly due to hexenuronic acids and metal compounds removal, once these substances directly react with the reagents used in the kappa number analysis and affect it, this way. It has also been observed that sequences including AHT stage presented lower costs in the bleaching process. According to the results it was concluded that the high temperature acid stage propitiated a cost reduction in bleaching reagents and the presence of hydrogen peroxide into the alkaline extraction stage is not necessary, because this reagent has minimally modified the final pulps' brightness compared to the pulps submitted to alkaline extraction without H2O2.
Keywords: Acid hydrolysis stage; Cellulose; ECF bleaching